COMPARISON AND PETROCHEMICAL CORRELATION OF SIMILAR GRANITOID FORMATIONS OF WESTERN TRANSBAIKALIA AND THE UKRAINIAN SHIELD - KOSTENKO, N.V.; TOLSTOY, M.I. (Institute of Geological Sciences, NAS of Ukraine, 2013)
As a result of petrochemical and geochemical studies of granitoid formations of the Ukrainian Shield and Western Transbaikalia by methods of mathematical statistics revealed that in the Ukrainian shield analogue of ore-bearing granite Hudzhyr complex can be granites of Kamennye Mogily complex. Specified as positional placement of a number of granitoid complexes of the Western Transbaikalia in the scheme of acid groups in the region.